Die Wiederkehr des Verdrängten am Beispiel des Ekels: Zum Betrachten der Folterbilder aus Abu Ghraib - Lorey, Isabell (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2005)
One year ago in German feuilletons, disgust and abhorrence were one of the first reactions on the publication of the photos of torture. Especially on the photos with Lynndie England. The paper follows this reactions of disgust and asks for the meaning of the pictures in the cultural imaginary of the west.